Evaluating impacts of climate variability on smallholder livelihoods and adaptation practices in the western Shewa Zone, Oromia, Ethiopia - Hordofa, Lelisa; Yazew, Tamiru (Frontiers in Climate, 2023)
The objective of this research was to assess the trends and variability in the Bako Tibe district as well as raise awareness among rural farmers. The sample of homes included 141 out of 29 participants, all from families headed by a female. The Mann-Kendall trend test and the Sen-slope estimator were used to assess the trend of annual minimum and maximum temperatures and seasonal precipitation for the study areas. The year, summer, and spring climate variability results were examined, and the CV of spring precipitation was found to be 34.8%, indicating high variability of rainfall. Spring precipitation was more unstable than summer precipitation. Statistically, total annual precipitation, the summer season, and the autumn season all showed positive or no significant trends, while spring and winter precipitation both showed a negative or decreasing trend. The probability of 7, 10, 15, and 20-day dry spells in June, July, August, and September during the main rainy season (summer) was zero. The chance of a 20-day dry spell occurrence was highest from March 1 (61 days) to April 23 (115 days), lowest from April 23 (130 days) to June, July, August, and September 20 (265 days), and highest after the end of September. The dry period lasted 15 days, beginning on March 1 (61 days), ending on May 8 (130 days), and returning to zero from May 8 (130 days) to June, July, August, and September 5 (250 days). The probability of a 10-day dry spell began in March (61) and ended on May 23 (145), with the 7-day dry spell ending on June 23 (160). In this study, annual precipitation and temperature values from 2010 to 2019 were examined. Precipitation and temperature have a positive and significant relationship with corn and teff. Approximately 65.2% of the population reported late precipitation, while 34.8% reported no late precipitation. A premature end to the rains affected the livelihoods of approximately 73% of those polled. Crop diversification, terracing, tree planting, irrigation cultivation for precocious crops, and non-agricultural activities have all been used to adapt to the effects of climate variability and change.